Charge separation and interfacial selectivity induced by synergistic effect of ferroelectricity and piezoelectricity on PbTiO3 monocrystalline nanoplates. (July 2020) - Feng, Yawei; Xu, Mengjiao; Liu, Hui; Li, Wei; Li, Hexing; Bian, Zhenfeng
Abstract: Charge separation and surface chemistry are essential for photocatalytic reaction, which is challenging to manipulate the performance of catalyst. In this work, the effects of ferroelectric and piezoelectricity (piezophototronics) properties on photocatalytic properties were studied in detail by using PbTiO3 monocrystalline nanoplates (PMNs). Visualization of charge distribution on the surface of PMNs was carried out by noble metal loading and selectivity dependence of crystal surface was revealed by choosing organic molecules with different charge properties. The apparent quantum efficiency (AQE) for photocatalytic water splitting can be promoted to 6.5 times by the ferroelectric/piezoelectricity synergistic modulation of the internal carriers and the interaction with the matrix. This strategy based on the coupling of ferroelectricity and piezoelectricity provides a new idea for the preparation of highly active photocatalysts and the improvement of photocatalytic performance. Graphical abstract: Image 1 Highlights: The interfacial reactions of free charges and charged/non-charged substrates were revealed. The reaction activity and selectivity are controlled by the polar crystalline facets. Regulating the crystalline facets polarization has no limitation on substrates and reactions.